Rotator Cuff Repairs Using Double-Row Modified Mason-Allen Stitches Resulted in Superior Clinical Outcomes at 2-Year Follow-Up Compared to the Double-Row Suture-Bridge Technique: A Case-Control Matching Study - W.P. Yau, M.B.B.S., F.R.C.S.Ed., F.R.C.S.Ed. (Ortho), F.H.K.C.O.S., F.H.K.A.M. (Orthopaedic Surgery) (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To compare the clinical outcomes of rotator cuff repair using a double-row modified Mason-Allen stitch (DR-MA) with those repaired with a double-row suture bridge (DR-SB). Methods: A retrospective case-control matching study was conducted to compare the results of patients who received complete supraspinatus tendon repair using a DR-MA configuration and a DR-SB pattern between 2009 and 2020. Exact matching was performed for patients with intact rotator cuff repair at postoperative magnetic resonance imaging. The matching criteria included sex, workers’ compensation, smoking status, hyperlipidemia, size and retraction of tear, and acromioplasty. Clinical outcomes, including visual analog scale (VAS), American Shoulder and Elbow Surgeon (ASES) score, and active shoulder forward flexion (FF), were documented at the 2-year follow-up. The percentage of patients who achieved minimum clinically important difference (MCID) was reported. Results: A total of 64 patients, including 28 men and 36 women, were matched, and the 2-year follow-up rate was 100%. All patients received postoperative magnetic resonance imaging at 19 ± 11 months. Significant improvement in all clinical outcomes was observed, regardless of the repair pattern (P < .001). The 2-year VAS was better in the DR-MA group compared to the DR-SB group (1.5 ± 2.0 and 2.9 ± 2.6, respectively; P = .009). At the 2-year follow-up, 91%, 90%, and 63% of patients in the DR-MA group achieved MCID in VAS, ASES, and FF, respectively. There was no difference in the proportion of patients achieving MCID between the 2 treatment arms. However, a more substantial improvement in VAS (P = .008), ASES (P = .014), and FF (P = .039) between preoperation and the 2-year follow-up was noted in the DR-MA group. Conclusions: No clinical differences in pain or function were found between DR-MA and DR-SB despite small and statistically significant differences in favor of DR-MA. Level of Evidence: Level III, retrospective cohort study.